Les critères de classement des catégories grammaticales - une perspective diachronique - Bulikowski, Brunon (Studia Romanica Posnaniensia, 2001)
This paper deals with different ways of classifying grammatical categories, from the antiquity to the present. The author refers to the works of Aristotle as well as to ideas of American and European structural grammarians. A large part of this article is devoted to an explication of the medieval Modistes theory of speculative grammar. This paper is also concerned with the opposition between grammatical and logical criteria.